Edukasi tentang Hipertensi bagi Kader dan Lansia Hipertensi di Posbindu Penyakit Tidak Menular: Education about Hypertension for Cadres and Hypertension Elderly at Posbindu Non-Communicable Diseases - Sukmawati, Sukmawati; Nurarifah, Nurarifah; Nitro, Galenzo (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2023)
Introduction: Efforts to handle non-communicable diseases, including hypertension, are trying to be formed based on cooperation and support from all elements of society who care about disease control through Posbindu PTM. Apart from early detection of hypertension, sufferers who have been given treatment are also expected to continue to regularly control their health at Posbindu PTM. Posbindu PTM activities in North Luwuk District include health promotion and services by cadres and supported by North Luwuk Health Center UPT health workers. In North Luwuk District, based on visit data, almost all of them are elderly category of hypertension sufferers. This community service aims to provide education about hypertension to cadres and elderly people with hypertension. The method of this educational activity is by means of counseling using leaflet media. The activity will be carried out on October 3 2023. The target is 35 people consisting of cadres and elderly people with hypertension. The results of the post test evaluation show an increase in knowledge after education. Advice to the target, it is hoped that they will continuously refresh their knowledge about hypertension so that early detection is maximized and they are able and willing to control their health.